Use of permeable pavement as a compensatory alternative for urban drainage in Recife-PE - Menezes, Lucas Amorim Amaral; Cabral, Jaime Joaquim da Silva Pereira (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The accelerated process of urbanization in recent decades changes the global population organization and brings modifications to cities, directly affecting the environment. The emergence of alternative solutions, such as permeable pavements, incorporate sustainable concepts and reshape the drainage system to adapt to faster and more critical flood hydrographs, aiming to reduce the impacts of urbanization. This study aimed to analyze the feasibility of using a permeable pavement, performed at the Polytechnic School of the University of Pernambuco (POLI-UPE), as a compensatory alternative in urban drainage, assessing the system and its hydraulic behavior. The methodology followed the stages of subgrade characterization; characterization and compliance analysis of the materials of the pavement layers; and evaluation of the hydraulic performance of the permeable pavement, conducting permeability tests, hydraulic simulations of precipitation, and evaluation of the largest rainfall event, in the analyzed period from March to May 2023. The results indicated a subgrade soil of good quality and base layer material in normative compliance. On the other hand, the material used in the laying and the compressive strength of the coating blocks were non-compliant, but without negative influence on usage for the period. The hydraulic performance of the pavement was analyzed, presenting a high permeability coefficient recently built (3.26 x 10-3 m/s) and good behavior in the simulations of intense rainfall and in the natural rainy event. The permeable pavement allowed infiltration and, consequently, reduction of the total runoff volumes, characterizing itself as a potential mitigation of urban flooding